Correlation Analysis Between Comfort and Mechanical Properties of Sports Fabrics (Journal of Fiber Bioengineering and Informatics, 2024)
Given the time-consuming and costly measurement of heat-moisture comfort indexes and the difficultyof quantifying contact comfort, 20 sports fabrics were tested for air permeability, moisture permeability,thermal resistance, moisture resistance, sensory evaluation indicators and 18 mechanical parameters.Then, the correlation between contact comfort indexes and mechanical parameters was analysed. Onthis basis, multiple linear regression prediction models for thermal resistance, moisture resistance andcontact comfort indexes of sports fabrics were established. The results show that the thermal resistanceof sports fabrics can be predicted by Compression work (CW) and Compression recovery rate (CRR)indicators, and the moisture resistance can be predicted by Bending work in the warp (BWa) and CRRindicators. The smoothness of sports fabrics can be predicted by CW and Compression stiffness (CAR),the softness by Bending work in weft (BWe) and CAR, the warmth by CW, BWe and Surface frictioncoefficient in weft (SFCe), and the combined feeling by Bwe and CAR. The models were also validatedand are considered to have practical implications for companies and consumers when assessing andimproving the comfort of sports fabrics.
Keywords: Sports Fabrics; Heat-moisture Comfort; Contact Comfort; Mechanical Properties; Regression Models